Loss of consciousness, collapse and associated driving restrictions: a retrospective case note review – an important reminder regarding driving restrictions. Issue 2 (May 2017) - Williamson, Adam; Muir, Scott
Background and aims: National guidelines outlining medical standards for fitness to drive are provided by The Driver and Vehicle Licensing Agency. We aimed to establish whether patients presenting with collapse or loss of consciousness received documented advice regarding driving restrictions, if appropriate for their working diagnosis. Methods and results: A retrospective case note review was undertaken over a four-month period for emergency patients clinically coded as seizure/convulsion (R568) and collapse/syncope (R55X); 163 patients had a primary or working diagnosis on discharge that suggested driving status and restrictions could have been reviewed. Six groupings of diagnoses were noted, and variation was seen amongst documentation for each. Current driving status was documented for 32 patients, and 34 had restriction advice documented; 73% (119 patients) had further investigations or clinic review planned. Conclusion: Documentation of driving status and restrictions is poor. This audit serves to remind clinicians of the importance of considering driving status when discharging patients who have presented with collapse or loss of consciousness. Recent high-profile media coverage regarding medical driving restrictions, both locally and nationally, have emphasised the need for knowledge of The Driver and Vehicle Licensing Agency guidance.